An Application of Electronic Program to Manage the Laboratory Quality Ranking in the University of Mosul - Haifa Saadoon; Shaymaa Razoqi (College of Education for Pure Sciences, 2024)
Laboratories are an essential part of the educational process in university faculties because of their importance in delivering scientific and applied material to students. There is great importance to the availability of safety conditions, professional staff, technical capabilities, and other laboratory requirements. Given the importance of quality in educational laboratories, the ranking of its must be done frequently. The evaluation information must be sound and available when needed. The objective of this research is to create an electronic Laboratory Quality Ranking (LabQR) program that simulates the paper evaluation process. The program converts all documents to electronic documentation and extracts the final score of the required conditions. Also, all the attached documents were saved in electronic databases, such as course certificates for employees and administrative orders. The program also provides ease of searching, retrieval, and archiving. The expansion and flexibility features have been considered in the program by adding other colleges, departments, and universities.